2015
DOI: 10.2961/jlmn.2015.02.0002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Pressure Waves in Confined Laser Ablation

Abstract: Nanostructure formation on bulk metals (copper, gold, and silver) by picosecond (FWHM = 10 ps) Nd:YAG laser irradiation was studied aiming at the production of low-reflectivity surfaces. The experiments were performed at two distinct wavelengths (λ = 355 and 1064 nm) using 20 kHz repetition frequency. The fluence was varied in the 1-11 J/cm 2 range, while the samples were shot by an average pulse number from 0 to 50 depending on the scanning speed of the applied galvanometric scanner. The reflectivity of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…As for the physical mechanism of ejection, it depends on a few parameters, such as laser pulse energy, laser pulse duration, and thickness of the film. In previous reports, it was found that the shock wave produced the force to push the cells when the laser pulse duration was at the level of picosecond or femtosecond ( 31 , 32 ). When the pulse duration was at the level of nanosecond or longer, the gas pressure was dominated ( 25 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the physical mechanism of ejection, it depends on a few parameters, such as laser pulse energy, laser pulse duration, and thickness of the film. In previous reports, it was found that the shock wave produced the force to push the cells when the laser pulse duration was at the level of picosecond or femtosecond ( 31 , 32 ). When the pulse duration was at the level of nanosecond or longer, the gas pressure was dominated ( 25 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ejection mechanism of LIFT is dependent on thickness of the coating layer, material, and laser power and duration, but the basic setup is similar ( 24 ). When a laser pulse shines on the surface of the coating layer, it will absorb the laser energy and vaporize, and the material on it will be pushed away under the gas pressure ( 25 30 ) or shock wave ( 31 , 32 ) induced by heating.…”
Section: Introductionmentioning
confidence: 99%
“…An energy absorption layer is coated on a transparent substrate which we called donor, and then the material to be printed is spread onto the donor. When a laser pulse propagates through the transparent substrate and focuses onto the surface of the energy absorption layer, the energy absorption layer will be heated to vaporize, and the material on it will be pushed away under the gas pressure (22)(23)(24)(25)(26)(27) or the shock wave (28,29) induced by heating.…”
Section: Introductionmentioning
confidence: 99%
“…During experiments, we observed bright spots remaining on the coverslip after ejection ( Figure 2C ). The spectra of these bright spots ( Figure S4C ) were distinguishable from those of PS or PMMA ( Figure S4A ), indicating that these bright spots might have been caused by the deformations in the TiO 2 coating (45, 46).…”
Section: Resultsmentioning
confidence: 99%